NASM essentials of corrective exercise training - Clark, Michael A.; Lucett, Scott; Sutton, Brian G. (Jones & Bartlett Learning, 2011)
NASM Essentials of Corrective Exercise Training introduces the health and fitness professional to NASM's proprietary Corrective Exercise Continuum, a system of training that uses corrective exercise strategies to help improve muscle imbalances and movement efficiency to decrease the risk of injury. This textbook includes several new chapters that were not included in NASM's previous corrective exercise materials, including the rationale for corrective exercise training, assessments of health risk, static postural assessments, range of motion assessments, and strength assessments (manual muscle testing) as well as corrective exercise strategies for the cervical spine, elbow, and wrist